Evaluation of the effect of cognitive therapy on perioperative anxiety and depression among Nigerian surgical patients (2003)
Study Objective: Surgical patients have been known to benefit immensely from psychological intervention. This study sets out to assess the pre and post operative anxiety levels and depression and the effect of cognitive therapy among Nigerian surgical patients. The effects of gender and educational status on preoperative anxiety and depression were also evaluated. Study design: The study utilized a controlled outcome design to evaluate the efficacy of self- instructional training (SIT) and rational emotive therapy (RET) in surgical patients. Preoperative anxiety and depression scores were used as co-variants. Patients: Thirty-three (33) elective surgical patients were sampled randomly, divided into three groups of eleven (11) patients each. Eight (8) subjects underwent gynaecological procedure while the remaining 25 subjects had general surgical procedures. The mean age was 32.72± 15.83 years (range= 17-16 years). Measurements: the major instruments used in the study were the State Anxiety Subscale of the Speilberger State Trait Anxiety Inventory (STAI) and Hospital Anxiety and Depression Inventory. Main results: AIT had the potential to reduce anxiety levels among subjects postoperatively (t=2.06; df-10; p<0.05). The use of RET reduced depression among surgical patients (t=1.23; df=10; p<0.05). Conclusions: it was concluded that surgical patients manifest varying degrees of anxiety preoperatively and postoperatively. Patient’s pre and postoperative anxiety and depression can be reduced by the introduction of SIT and RET.